PENGARUH LEVERAGE, LIKUIDITAS, PROFITABILITAS, UKURAN PERUSAHAAN DAN SAHAM PUBLIK TERHADAP PENGUNGKAPAN SUKARELA LAPORAN KEUANGAN PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2014-2017 - Dian Alinda Saraswati, 15.05.52.0349; Nuswandari, Cahyani (Students' Journal of Accounting and Banking, 2019)
This study aims to examine the influence of leverage, liquidity, profitability, firm size, and public shares on the broad disclosure of voluntary financial statements. The data used in this study are secondary data, in the form of company financial statements. To find out the variables that most influence the broad disclosure of financial statements. The number of research samples is 327 companies and in outliers to 324 companies. The sampling method used in this study was purposive sampling using certain criteria. The data was then tested with descriptive statistics, normality, multicollinearity, autocorrelation and heterocedasticity. The results of the study show normal data and are free from violations of classical assumptions. The next analysis is the use of multiple linear regression to explain the influence between these variables. The results of the analysis can be concluded that leverage has no significant negative effect on the completeness of financial statement disclosures, profitability has a positive and insignificant effect on the completeness of financial statement disclosures, company size and liquidity have a significant negative effect on the completeness of financial statement disclosures, and public shares have a significant positive effect on report disclosure completeness finance.